Self-service technology for hypermarket checkout - Hassan. H; Sade. A.B.; Rahman. M.S. (Canadian Center of Science and Education, 2013)
The self-service technology innovation in hypermarket retailing has led to the shopping activity being served by the shopper themselves without relying on any service provider. However, this concept is still not implemented in Malaysia where the self-service concept is still supported by the service provider at the checkout station. This paper is suggesting that a new innovation should be implemented in the Malaysian hypermarket retailing industry by adopting self-service technology at the hypermarket checkout station. This research is developed based on observation conducted at various hypermarket retailing outlets within Malaysia. The findings from the general literature reviews are also gathered to strengthen the existing idea. The focus of this research is on the hypermarket retailing industry within Malaysia, especially in urban areas. Due to the modernization of the shopping trend, it is suggested that the timing might be right to explore implementing the concept of entirely self-service at hypermarkets in Malaysia to enhance the flow efficiency and effectiveness of the checkout operations. It is strongly believed that the introduction of this completely self-service shopping experience will be highly adopted, especially by the young generation in urban areas. This research explores the opportunity to enhance hypermarket retailing operations by upgrading the existing manual checkout station into self-service checkout stations using modern technology. It is expected that the idea for a totally self-service checkout system could be implemented in practice through the robust findings from this research